Distribution of Rickettsia rickettsii in ovary cells of Rhipicephalus sanguineus (Latreille1806) (Acari: Ixodidae) - da Silva Costa, Luis Flavio [UNESP]; Nunes, Pablo Henrique [UNESP]; Soares, Joao Fabio; Labruna, Marcelo Bahia; Camargo-Mathias, Maria Izabel [UNESP] (Biomed Central Ltd., 2011)
Background: Considering the fact that the dog tick, Rhipicephalus sanguineus, has a great potential to become the vector of Brazilian Spotted Fever (BSF) for humans, the present study aimed to describe the distribution of the bacterium Rickettsia rickettsii, the etiological agent of BSF, in different regions of the ovaries of R. sanguineus using histological techniques. The ovaries were obtained from positive females confirmed by the hemolymph test and fed in the nymph stage on guinea pigs inoculated with R. rickettsii.Results: The results showed a general distribution of R. rickettsii in the ovary cells, being found in oocytes in all stages of development (I, II, III, IV and V) most commonly in the periphery of the oocyte and also in the cytoplasm of pedicel cells.Conclusions: The histological analysis of the ovaries of R. sanguineus infected females confirmed the presence of the bacterium, indicating that the infection can interfere negatively in the process of reproduction of the ticks, once alterations were detected both in the shape and cell structure of the oocytes which contained bacteria.
Keywords: Rickettsia rickettsii; Rhipicephalus sanguineus; Brazilian Spotted Fever; ovary; histology